Kaleidoscope eyes - Bryant, Jennifer (Knopf, 2009)
In 1968, with the Vietnam War raging, thirteen-year-old Lyza inherits a project from her deceased grandfather, who had been using his knowledge of maps and the geography of Lyza's New Jersey hometown to locate the lost treasure of Captain Kidd.